Response to selpercatinib in a patient with RET fusion-positive pulmonary large-cell neuroendocrine carcinoma: A case report - Arora, Aakriti; Zaemes, Jacob; Ozdemirli, Metin; Kim, Chul (Frontiers in Oncology, 2023)
Large cell neuroendocrine carcinoma (LCNEC) is a rare subtype of non-small cell lung cancer associated with poor prognosis. LCNEC is genetically heterogeneous, and studies have revealed distinct molecular subtypes of LCNEC, which may have therapeutic implications. Herein, we present a case of a patient with stage IV LCNEC harboring KIF5B-RET fusion whose disease responded to the selective RET inhibitor selpercatinib both extra- and intra-cranially, highlighting the importance of comprehensive molecular testing in LCNEC for selection of optimal treatment.